2010
DOI: 10.1017/s0003055410000110
|View full text |Cite
|
Sign up to set email alerts
|

Migrant Remittances and Exchange Rate Regimes in the Developing World

Abstract: This article argues that the international financial consequences of immigration exert a substantial influence on the choice of exchange rate regimes in the developing world. Over the past two decades, migrant remittances have emerged as a significant source of external finance for developing countries, often exceeding conventional sources of capital such as foreign direct investment and bank lending. Remittances are unlike nearly all other capital flows in that they are stable and move countercyclically relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
76
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(85 citation statements)
references
References 104 publications
4
76
1
Order By: Relevance
“…While remittances have been considered as a facilitation of external financing constraints and thus a source of investment for developing countries, they might also trigger Dutch disease phenomenons such as real exchange rate appreciation and, eventually, a weakening of international competitiveness (López et al 2008;Acosta et al 2009). The evidence on the effect of remittances on output growth is also mixed, with some studies showing a positive influence on growth (Giuliano and Ruiz-Arranz 2009) while others do not find such effects (Yang 2011). Singer (2010 finds that inflowing remittances affect exchange-rate regimes, and hence provides evidence that policy in receiving countries is responsive to incoming remittances.…”
Section: Relevant Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…While remittances have been considered as a facilitation of external financing constraints and thus a source of investment for developing countries, they might also trigger Dutch disease phenomenons such as real exchange rate appreciation and, eventually, a weakening of international competitiveness (López et al 2008;Acosta et al 2009). The evidence on the effect of remittances on output growth is also mixed, with some studies showing a positive influence on growth (Giuliano and Ruiz-Arranz 2009) while others do not find such effects (Yang 2011). Singer (2010 finds that inflowing remittances affect exchange-rate regimes, and hence provides evidence that policy in receiving countries is responsive to incoming remittances.…”
Section: Relevant Literaturementioning
confidence: 99%
“…These large monetary inflows affect microand macroeconomic outcomes in the receiving countries. For example, the literature has demonstrated that remittances affect the quality of governance (Ahmed 2012;Ahmed 2013;Berdiev et al 2013), financial sector development (Giuliano and Ruiz-Arranz 2009;Aggarwal et al 2011), exchange rate regimes (Singer 2010), international competitiveness (López et al 2008;Acosta et al 2009) and schooling decisions (Edwards and Ureta 2003;Alcaraz et al 2012;Ambler et al 2015). 1 Despite their enormous importance, little research exists on the relevance and impact of inflowing remittances for public finances of receiving countries.…”
Section: Introductionmentioning
confidence: 99%
“…Whether remittances constitute yet another resource curse that may feed government corruption is another subject on the research agenda (Tyburski, 2012(Tyburski, , 2014. Surprisingly, the impact that remittances may have on governments' policy choices has been less researched (Ketkar & Ratha, 2010;Leblang, 2010;Singer, 2010). In particular, there is practically no evidence as to how governments may alter their provision of social welfare and public goods in the presence of family remittances, which substitute for those goods and provide a form of private insurance (Ebeke, 2011).…”
Section: Financial Remittances and The Statementioning
confidence: 99%
“…These large monetary inflows affect microand macroeconomic outcomes in the receiving countries. For example, the literature has demonstrated that remittances affect the quality of governance (Ahmed 2012;Ahmed 2013;Berdiev et al 2013), financial sector development (Giuliano and Ruiz-Arranz 2009;Aggarwal et al 2011), exchange rate regimes (Singer 2010), international competitiveness (López et al 2008;Acosta et al 2009) and schooling decisions (Edwards and Ureta 2003;Alcaraz et al 2012;Ambler et al 2015).…”
Section: Introductionmentioning
confidence: 99%